The strategic direction of the interaction between agricultural enterprises and enterprises with other types of the economic activities - Tisunova, V. M.; Mardar, D. O. (Видавництво Львівської політехніки, 2014)
The leading role of the agricultural production in the priority economic activities is shown in the article; there are summarized trends of organizational approximation of production of agricultural products to industrial production, industrial Donbass taken as an example; the prospects of creation conglomerates are discussed to ensure food self-sufficiency of the region. Appropriate recommendations are provided. Показано провідну роль сільськогосподарського виробництва серед пріоритетних видів економічної діяльності, узагальнено тенденції організаційного наближення випуску сільськогосподарської продукції до промислової діяльності на прикладі індустріального Донбасу, розглянуто перспективи створення конгломератів для забезпечення продовольчої самодостатності регіону та надано відповідні рекомендації.
Стратегічний напрям взаємодії сільськогосподарських підприємств з підприємствами інших видів економічної діяльності
Keywords: agricultural business; economic activities; strategy; conglomerate; food selfsufficiency; region; сільськогосподарське підприємство; види економічної діяльності; стратегія; конгломерат; продовольча самодостатність; регіон